Uncovering potential targets for antibody-drug conjugates in the treatment of gynecologic malignancies - Jiang, Yuying; Xu, Yuance; He, Junqi; Sui, Lei; Li, Tian; Xia, Nannan; Yao, Qin (Frontiers in Pharmacology, 2025)
BackgroundAntibody-drug conjugates (ADCs) play an important role in the targeted therapy of gynecological malignancies. The purpose of this study was to investigate the expression of targets in gynecologic malignancies in order to predict the selection of targets for the development of antibody-drug conjugates.MethodsIn this article, we identified existing ADCs and their targets through clinical trial databases and public genomic datasets, performed differential analysis of tumor antigen targets (TATs) expression between tumor and normal tissues, and evaluated the necessity of the targets for tumor cell lines.ResultsIn gynecologic malignancies, we have identified several highly expressed TATs, some of which have been targeted by FDA-approved ADCs, such as TROP2 and Nectin-4, although these drugs have not been approved for the treatment of gynecologic cancers. At the same time, we also observed that some targets of ADCs that have not yet been approved by the FDA also show high expression levels in gynecologic malignancies tissues, such as MSLN, ERBB3, NaPi2b, etc. Furthermore, we identified TATs with high expression levels in various pathological subtypes of ovarian, endometrial, and cervical cancer. Notably, some TATs are crucial to the survival of tumor cells, such as CD71, TOP1, and TDGF1, which are essential for the survival of ovarian, endometrial, cervical, and other tumor cells.ConclusionWe have innovatively predicted the potential targets of ADCs in treating gynecological malignancies and provided a new perspective on applying some FDA-approved ADCs in indications for gynecological cancers.